Comparison of efficacy of Ledermix and Calcium hydroxide in the management of deep caries (Update Dental College Journal, 2020)
Background:Pulp capping is a treatment that enables pulp to recover and maintain its vitality and function by applying a protective agent to an exposed pulp. Ca (OH)2 has been considered the gold standard for this procedure. Despite its wide use, Ca (OH)2 is not ideally suited for pulp capping. Recently ledermix cement used for indirect pulp capping material in the outer world broadly.Objective: To assess the clinical and radiological evidence of the formation of secondary dentin and compare the degree of short time post operating pain after indirect pulp treatment.Methods: A Randomized control trial in vivo study was directed in the Department of Conservative Dentistry and Endodontics, Faculty of Dentistry, Bangabandhu Sheikh Mujib Medical University for one year (January 2012-January 2013). We took the patients with 40 deep carious permanent teeth as a sample. The selected teeth were divided into two test groups. All odd number teeth (20) were included in group-1(where pulp capping was done with ledermix cement). All even number teeth (20) were included in group-2(where pulp capping was done with Ca(OH)2). We assessed all the patients clinically and radiographically at the interval of 3, 6, and 12 months simultaneously for the assessment of dentinal bridge formation and also collected data was analyzed using statistical package for social science (SPSS) version 17.Results: Among the full scale 40 models, ledermix (20) and Ca(OH)2(20), minor to direct irritaion of the teeth was experienced premium to treatment and found comparable in the two gatherings. Regardless, after 24 hrs of treatment, this value was shockingly higher in the Ca(OH)2 (p